Innovation of Augmented Reality Based Flash Card Learning Media Assisted by Assembler Edu to Improve Students’ Learning Outcomes on the Topic of Traditions and Local Community Culture - Gunawan Ali; Wiwik Okta Susilawati; Desy Fitriana (The Future of Education Journal, 2025)
This study is grounded in challenges encountered in the teaching and learning process, namely the limited use of instructional media during content delivery and the low level of students’ learning interest, which ultimately affects their learning outcomes. Therefore, this study aims to develop augmented reality–based flash card learning media assisted by Assembler Edu. This media is expected to improve students’ learning outcomes in the subject Traditions and Culture of the Surrounding Community, as well as to meet the criteria of validity, practicality, and effectiveness. The method employed in this study is Research and Development (R&D) using the ADDIE development model. The stages of the ADDIE model consist of Analysis, Design, Development, Implementation, and Evaluation. The results indicate that the developed learning media demonstrates a high level of feasibility. Language validation reached 0.809, content validation 0.777, graphical validation 0.866, test-item validation 0.888, and teaching module validation 0.827. In terms of practicality, educators’ responses reached 100%, while the average response from students was 80.66%, indicating that the media is highly practical for classroom use. Regarding effectiveness testing, 86.36% of students achieved mastery learning, which falls into the very effective category, demonstrating that the learning objectives were successfully achieved.